Studie koncepce řízení oběhu obalů ve společnosti Bosch Diesel s. r. o. - Mahdalová, Eva (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Diplomová práce se věnuje problematice řízení v oblasti obalového hospodářství. Pomocí metod využívaných v logistice a modelovacího nástroje ARIS bude provedena analýza stávajícího stavu a z ní odvozeny problematické oblasti. Následně bude navržen takový koncept řízení, který by tyto oblasti eliminoval a tak proces řízení zefektivnil, zautomatizoval a představoval celkové snížení logistických nákladů.

This diploma thesis deals with the issue of packaging management. Using methods employed in logistics and modeling tool ARIS, the analysis will examine the current situation and its related problem areas. Subsequently, there will be designed such a management concept that would eliminate these areas in order to make the management process streamline, automate and to lead to overall reduction in logistics costs.
The Study of Conception of Management of Wrappage in Bosch Diesel s. r. o.
Keywords: Logistické řízení; logistický řetězec; obaly; reengineering logistických procesů; metody a nástroje reengineeringu.; Logistics management; logistics chain; packaging; logistics reengineering of processes; reengineering methods and tools.